Primed Low Frequency Transcranial Magnetic Stimulation Effects on Smoking Cue-Induced Craving - Flores-Leal, M; Sacristán-Rock, E; Jiménez-Ángeles, L; Azpiroz-Leehan, J (Revista Mexicana de Ingenieria Biomedica, 2016)
Repetitive Transcranial Magnetic Stimulation (rTMS) has shown the potential to reduce craving to smoke and the amount of cigarettes smoked. When low frequency rTMS is preceded by a priming session the cortical inhibitory effects are enhanced provoking a lasting performance. In this study we evaluate the brain regional activations and self-reported mood effect of one session of primed low frequency rTMS over the left dorsolateral prefrontal cortex (DLPFC) in response to smoking-related cues during temporary nicotine abstinence. Ten moderate nicotine-dependent subjects participated in a crossover design, comparing a single session of active versus sham stimulation. After treatment, a functional Magnetic Resonance Imaging (fMRI) study was performed on all participants while completing a block-design cue reactivity paradigm. Our measures also included self-reported craving and mood score before and after every rTMS session. The number of daily smoked cigarette in a one week around period was also recorded. The results show that self-reported cravings were lower following the active stimulation; significant activation was found in areas associated with emotion control (anterior cingulate gyrus and subgenual area) and episodic memory (precuneus and posterior cingulate gyrus) as a result of the stimulation. No significant difference was found in the number of cigarettes smoked and mood scores between the sham and active condition during the one week period records. This study confirms the previous evidence that rTMS can reduce cigarette cravings and provides evidence of the neural mechanism of action that take place in order to achieve these neuromodulation effects.